React Native Cookbook : Step-By-step Recipes for Solving Common React Native Development Problems - Ward, Dan (Packt Publishing Ltd, 2019)
React Native is perfect for creating mobile applications with maximized code reusability and cost saving. With this practical solutions guide by your side, you can build amazing UIs, tackle mobile development-related issues, and build high-performance apps for mobile environments.